Implementasi Software Santri dalam Penyusunan Laporan Keuangan sesuai Pedoman Akuntansi Pesantren (Studi Kasus Ma’had Miftahul Mahabbah Annawawy) - Nabillah, Athiyatul Zahra; Febriani, Dewi (Tazkia Islamic University College, 2024)
This study evaluates the implementation of the SANTRI Software using the Delon and Mclean model and applies the SDLC method and the Parallel method in preparing Islamic boarding schools' financial reports. Through a case study at Mahad Miftahul Mahabbah Annnawawy, data was collected through interviews, observation and analysis of related documents. The results show that the SANTRI Software has a positive impact on preparing Islamic boarding school financial reports according to accounting guidelines. This software improves efficiency and accuracy in collecting, processing, and reporting financial data. The findings of this study can be used as a reference for other Islamic boarding schools in adopting the SANTRI Software to improve their financial management. The importance of implementing the Delone and McLean Model, the SDLC method, and the Parallel method in implementing SANTRI software is also emphasized to achieve successful implementation and user satisfaction.